Long-Term Effectiveness and Cost Effectiveness of Multiple Myeloma Treatment Strategies for Elderly Transplant-Ineligible Patients in Serbia - Vukićević Đurđa; Rochau Ursula; Savić Aleksandar; Schaffner Monika; Jevđević Milica; Stojkov Igor; Sroczynski Gaby; Willenbacher Wolfgang; Jahn Beate; Siebert Uwe (Sciendo, 2020)
Evidence on long-term effectiveness and cost effectiveness of treatment sequences for multiple myeloma (MM) is sparse. We used published data and country-specific data to assess the cost effectiveness of four-line treatment sequences for elderly transplant-ineligible patients with MM in Serbia.